2016
DOI: 10.1093/cercor/bhw265
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of BOLD fMRI Correlations

Abstract: Measurement of correlations between brain regions (functional connectivity) using blood oxygen level dependent (BOLD) fMRI has proven to be a powerful tool for studying the functional organization of the brain. Recently, dynamic functional connectivity has emerged as a major topic in the resting-state BOLD fMRI literature. Here, using simulations and multiple sets of empirical observations, we confirm that imposed task states can alter the correlation structure of BOLD activity. However, we find that observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
555
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(572 citation statements)
references
References 94 publications
16
555
1
Order By: Relevance
“…Evaluating motion (e.g. using frame-wise displacement or DVARS (Derivative of Root-mean-square VARiance over voxelS) and incorporating strategies to account for motion artifacts that go beyond rigid body realignment and regression of motion parameters are required (Laumann et al, 2016;Power et al, 2015;Satterthwaite et al, 2013). Data censoring or scrubbing, i.e.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…Evaluating motion (e.g. using frame-wise displacement or DVARS (Derivative of Root-mean-square VARiance over voxelS) and incorporating strategies to account for motion artifacts that go beyond rigid body realignment and regression of motion parameters are required (Laumann et al, 2016;Power et al, 2015;Satterthwaite et al, 2013). Data censoring or scrubbing, i.e.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…Indeed, recent studies using resting-state fMRI in humans reported that the temporal fluctuation of FC cannot be distinguished from that in a model assuming stationary FC and statistical sampling error [23,24]. Applying the same analysis to the mouse data, we found that, in both neuronal calcium and hemodynamic signals, the temporal dynamics of FC were not fully explained by stationary FC [16].…”
mentioning
confidence: 83%
“…Permutations in the frequency domain, which preserves the power spectrum but scrambles the phases of each node 101103 .…”
Section: Statistical Testingmentioning
confidence: 99%